Rheological and composition analyses of CO2 gas hydrates - Sandoval, Gustavo Alonso Barrientos (2019)
In the present work, it is investigated the rheological behavior of CO2 hydrates form from water-in-oil emulsions since high concentrations of this gas have been reported in the Brazilian Pre-salt oil wells, with large potential to form hydrates. To investigate this fact, a sequence of tests was conducted using an assembly composed by a rheometer, a magnetic pressure cell, and a high-pressure system, where similar pressure and temperature conditions were applied to those found in the petroleum industry. The novel results displayed in curves of viscosity over time are revealed in two main sections. Firstly, it is shown the effect produced by the shear rate, water volume fraction and salt impact on CO2 hydrates. It is also investigated the ability of the reconstruction of the CO2 hydrates and its memory effect. Secondly, results that indicate the effect produced on the induction time of hydrate formation by the addition of gas condensate and by the addition of small amounts of powder asphaltenes in the water-in-oil emulsions are shown. These interfacially active particles seem to act like kinetic hydrate inhibitors.